Efficacy of Psyllaephagus pistaciae (Hymenoptera: Encyrtidae) as a Biocontrol Agent against Agonoscena pistaciae (Hemiptera: Aphalaridae) using age-specific functional response - Hamid Rahimzadeh Behzadi; Mahdi Ziaaddini; Mohammad Amin Jalali; Fateme Ranjbar (نامه انجمن حشره‌شناسی ایران)
Psyllaephagus pistaciae (Hymenoptera: Encyrtidae) is the primary native biocontrol agent targeting the common pistachio psylla, Agonoscena pistaciae (Hemiptera: Aphalaridae), a major pest in Rafsanjan, the leading pistachio production region in Iran. In this study, how female parasitoid age influences the type of functional response was examined by daily assessing two behavioral traits—host feeding and parasitism—across different densities of pistachio psylla, within the context of age-specific functional response. The logistic regression analysis identified a type II functional response for P. pistaciae, characterized by an increased attack rate (parasitism + host feeding) with increasing psylla density. Notably, this response pattern was consistent across different female ages. In the first week of adulthood, wasps demonstrated optimal searching efficiency for both parasitism and host feeding. However, as female wasps aged, there was a progressive increase in handling time for parasitism and feeding activities. Peak searching efficiency for host attacks was observed on day 7, while the minimum handling time occurred on day 5. The highest levels of parasitism were observed on the fifth day of the female's lifespan, underscoring increased efficiency in parasitism and attack rates during the early stages of the parasitoid's life, especially within the first week. Moreover, both host density and parasitoid age significantly affected these rates.